2016
DOI: 10.1523/jneurosci.1125-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Silent Expectations: Dynamic Causal Modeling of Cortical Prediction and Attention to Sounds That Weren't

Abstract: There is increasing evidence that human perception is realized by a hierarchy of neural processes in which predictions sent backward from higher levels result in prediction errors that are fed forward from lower levels, to update the current model of the environment. Moreover, the precision of prediction errors is thought to be modulated by attention. Much of this evidence comes from paradigms in which a stimulus differs from that predicted by the recent history of other stimuli (generating a so-called "mismat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
142
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(159 citation statements)
references
References 45 publications
13
142
4
Order By: Relevance
“…Importantly, MMNm‐responses were also expected to be reduced in omission trials. Findings by Wacongne et al [] and others [Chennu et al, ] showed that omission responses are similar in latency and topography to the MMN response elicited by deviant sequences. Finally, we expected the P300m elicited by a violation of global regularities to be reduced in ScZ.…”
Section: Introductionmentioning
confidence: 74%
“…Importantly, MMNm‐responses were also expected to be reduced in omission trials. Findings by Wacongne et al [] and others [Chennu et al, ] showed that omission responses are similar in latency and topography to the MMN response elicited by deviant sequences. Finally, we expected the P300m elicited by a violation of global regularities to be reduced in ScZ.…”
Section: Introductionmentioning
confidence: 74%
“…Predictions modulate auditory evoked responses in an area specific manner, involve both the ventral and dorsal pathways (Kandylaki et al, 2016; Sohoglu and Chait, 2016), and affect both feedforward and feedback connections (Auksztulewicz and Friston, 2016; Chennu et al, 2016). While an informative visual context facilitates the correction of predictions about expected speech using incoming multisensory evidence, we can only speculate about a direct link between the reported effects and predictive processes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the particular neural populations and processing levels that are preferentially sampled by different recording techniques may be key to the study outcome. This may account for the fact that, in several instances, RS/ES effects that were observed with one noninvasive recording method were absent in another despite using otherwise identical paradigms 53,78,119 . This issue greatly complicates efforts to generate precise, empirically testable PP hypotheses and also reduces the scope for disconfirmatory results 42 .…”
Section: Hypothesis 1: Error‐signaling Neural Responses To Sensory Stmentioning
confidence: 99%
“…This may account for the fact that, in several instances, RS/ES effects that were observed with one noninvasive recording method were absent in another despite using otherwise identical paradigms. 53,78,119 This issue greatly complicates efforts to generate precise, empirically testable PP hypotheses and also reduces the scope for disconfirmatory results. 42 In recognition of this point, researchers are increasingly seeking to verify the other hypotheses of PP by attempting to isolate mechanisms underlying the generation of predictions and hierarchical inference, and it is to this literature that we now turn our attention.…”
Section: Hypothesis 1: Summary and Conclusionmentioning
confidence: 99%